Comparative analysis of mechanical strength in aluminum welding joints of AA 5052 and AA 6061 plates - Telaumbanua, Safitiar; Derlini, Derlini; Lubis, Yakmur (Trigin Publisher, 2025)
Oxy-Acetylene welding is a commonly used manual welding method due to its affordability and portability, as it does not require electricity. This process joins metal surfaces by heating them with a flame from burning a mixture of acetylene (C₂H₂) and oxygen (O₂), with or without filler metal, and without applying pressure. Aluminum, known for its lightweight, corrosion resistance, and good conductivity, is often alloyed with elements like Cu, Mg, Si, Mn, Zn, and Ni to enhance its mechanical properties. This study analyzes the mechanical properties and microstructure of Oxy-Acetylene welded aluminum alloys AA 5052 and AA 6061. Tests conducted include tensile, flexural (bending), and hardness tests. The tensile test showed AA 6061 had a higher tensile strength of 78.4 MPa, though still considered brittle due to the presence of weld defects. These defects were linked to the uneven melting and poor adhesion of the welding wire, resulting in gaps. The highest bending strength was also recorded by AA 6061 at 70.44 MPa with no fractures, while AA 5052 had the lowest at 50.1 MPa with fractures in the weld metal. Overall, Oxy-Acetylene welding on both materials showed imperfections due to inconsistent weld quality.